The susceptibility level and sustainability potential of groupers; Plectropomus sp. in a marine national park - M. Tadjuddah; . Abdullah; S. Kamri; N.I. Wianti (Global Journal of Environmental Science and Management)
Wakatobi National Park has a tropical marine ecosystem with typically dynamic aquatic resources, and it also has a potentially massive number of groupers such as red (Plectropomus leopardus) and black groupers (Plectropomus areolatus). However, the sustainability of the grouper resources has not been managed effectively and environmentally friendly. This study aims to determine the susceptibility level of red and black groupers in the research area based on the productivity and susceptibility analysis. This study was conducted from May to November 2018, in which the data were collected from the grouper’s fishermen using hand line with simple random methods as a fishing gear in Wanci and Tomia islands of Wakatobi. Based on the collected data, productivity attribute of red groupers is at 1.8, and the susceptibility level is at 2.08, while the black groupers have 1.7 for the productivity attributes and 2.0 for their susceptibility level. Based on the susceptibility index of both types of fish, it indicates that red groupers are at 1.61, and the black groupers’ susceptibility level is at 1.64. This study implies that the susceptibility index of red and black groupers at Wakatobi National Park is moderate which means that the groupers as a matter of fact experience fishing pressure. Therefore, some sustainable efforts to effectively and environmentally friendly manage the fishing activity in the island need to be done in the future.